Analisis Kinerja Perawat Pelaksana dalam Melaksanakan Dokumentasi Asuhan Keperawatan - Afriyanti, Desi (Jurnal Gema Keperawatan, 2025)
One standard for evaluating nurses' performance in implementing nursing care is assessing nursing care documentation. This objective assessment covers the following areas: assessment, nursing diagnosis, nursing intervention, nursing implementation, and nursing evaluation. Nursing care documentation is an important part of the ongoing nursing care process. Accurate and complete documentation ensures continuity of patient care, serves as a communication tool among healthcare professionals, provides legal accountability, and enables evaluation of the quality of healthcare services. This study aims to describe executive nurses' performance in implementing nursing care documentation. The research design is descriptive. The study population consists of 227 respondents, and a sample of 145 was selected using probability sampling techniques, specifically stratified proportional random sampling. This study uses a nursing performance questionnaire to measure nurses' performance in implementing nursing care documentation. The results indicate that executive nurses perform well in implementing nursing care documentation in inpatient wards, with an average score of 53.82. The study concludes that nurses perform well in implementing nursing care documentation.